'I Find it Daunting . . . That I'm Gonna Have to Deal with This until 60': Extended Working Lives and the Sustainable Employability of Operational Firefighters. (June 2023) - Egdell, Valerie; Hussein, Rima; Harrison, Deborah; Bader, Anna Katharina; Wilson, Rob
While operational firefighters in the UK fire and rescue service traditionally retired in their 50s, their working lives are now extending. However, external pressures and the emotional and physical demands of firefighting work, lead to questions about whether operational firefighters will be able to extend their working lives. In this article, we engage with Van der Klink et al.'s sustainable employability model, which focuses on situations that allow individuals to make valuable contributions through their work and reveal how working lives can be extended. We consider implications of the characteristics of operational firefighting work, individual circumstances and contextual factors for the extension of working lives. Drawing on interviews conducted with firefighters, crew managers and watch managers working in a UK fire and rescue service, we highlight the unsustainability of many future working lives because of wellbeing and organisational pressures.